20 solid state projects for the car & garage - Marston, R. M. (Newnes Technical Books, 1970)
20 Solid State Projects for the Car & Garage focuses on solid-state construction projects for use in the car and the garage, including ice-warning indicator, emergency-light flasher, electronic tachometer, and over-heat indicator.The book first elaborates on the capacitor-discharge ignition system, automatic parking light operator, and windshield wiper pause controller. The text then examines lights-are-on reminder, multi-input panel light flasher, ice-warning indicator, and over-heat indicator. Topics include how these solid-state construction projects function, basic and electronic versions.